Die Zulässigkeit der Legendierten Kontrolle unter besonderer Berücksichtigung der Legendierten Aktenführung - Funcke, Katharina (Schriften zum Strafrecht (SR), 2024)
»The Admissibility of Deceptive Controls with special consideration of Deceptive Documentation«: Covert and deceptive investigative measures are being used to an ever greater extent in the fight against organised crime - often without a specific legal basis. The publication deals with the constitutional and criminal procedural limits of the state's power to deceive by means of the investigative instrument of the deceptive control. It also focuses on the question of the legal admissibility of deceptive, i.e. incorrect or incomplete, documentation.